Genetic variability in guapuruvu Schizolobium parahyba progenies - Silva Chinelato, Fernanda Carolina (2014)
The guapuruvu is pioneer specie by fast growing of legume family with great importance in restoration projects. The aim of the study was to assess the genetic variability of offspring of Schizolobium parahyba through quantitative genetic parameters. The progeny test was installed in a randomized block design in three replications four plants per plot with 60 progenies. Was evaluated plant height, diameter at breast height with the ages: 2, 7, 14, 20 and 66 months and the percentage of survival at 66 months. For the estimates of genetic parameters, the data were analyzed by software SELEGEN. The heritability coefficients at individual level (ĥa2) were higher by height (0.318, 0.012, 0.247, 0.390 and 0.012) compared to DBH (0.021, 0.024 and 0.015) in the 14, 20 and 66 months, respectively. The highest genetic correlation between characters and plant height DBH occurred in the period of 14 months (0.85). The progenies studied, despite not show significant genetic variability, have the potential to initiate programs of forest breeding and for conservation genetics.